Kontekstualisasi Gharar di Era Digital: Tinjauan Fikih Muamalah terhadap Validitas Objek Akad (Ma'qud 'Alaih) pada E-Commerce - Aat Supriatna; Abdul Gofur (MUAMALAH: Journal of Islamic Economics and Business Law, 2026)
The rapid growth of the e-commerce ecosystem in Indonesia has fundamentally changed muamalah interactions from face-to-face patterns (mujwajahah) to virtual transactions without physical boundaries. However, this transformation leaves crucial Islamic legal issues, particularly regarding the physical absence of the contract object (ma'qud 'alaih) during the transaction. In classical fiqh discourse, the absence of the object (ghayb al-majlis) is often associated with gharar (uncertainty), which can invalidate the contract due to the high potential for fraud and information asymmetry. This study aims to reconstruct the concept of gharar in the context of the digital economy and formulate validity parameters for contract objects on e-commerce platforms based on contemporary Fiqh Muamalah perspectives. The method employed is normative legal research (juridical-normative) with a qualitative approach. The author collects data through library research on cross-madhhab classical books (turats), DSN-MUI fatwas, and marketplace regulations, which are then analyzed using content analysis techniques and the qiyas (analogy) method. The results indicate an epistemological shift in interpreting contract validity requirements. First, the concept of "seeing" (ru'yah) in the digital era has undergone an extensification of meaning; it is no longer limited to visual physical contact but transforms into ma'lum as-sifat (knowing the attributes) through specification descriptions, high-resolution photos, and demonstration videos. Second, the digital display mechanism has a legal basis equivalent to the Salam contract (forward sale), where the absence of goods is tolerated as long as the criteria are measurable (awshaf munbadhitah). The study concludes that contract objects in e-commerce are valid (sah) and free from gharar fahish (major uncertainty), provided they meet the principle of information adequacy. This validity is further reinforced by the integration of the return policy feature as a modern form of khiyar syarat and khiyar 'aib, which functions to protect consumer assets (hifz al-mal) from losses due to product discrepancies.